Transfer Modality Research Initiative: Impacts of combining social protection and nutrition in Bangladesh - Ahmed, Akhter; Hoddinott, John F.; Roy, Shalini (International Food Policy Research Institute, 2021)
In Bangladesh, social protection programs have the potential to uplift the most vulnerable out of poverty. Until recently, however, these programs have had little impact on nutrition. Results from a randomized controlled trial in Bangladesh – the Transfer Modality Research Initiative – provides the proof of concept that combining social safety net transfers with nutrition behavior change communication (BCC) can significantly improve household food security and child nutrition, and these impacts can be sustained over time.